GAMBARAN EFFISIENSI PENGGUNAAN TEMPAT TIDUR RUANG PERAWATAN KELAS III DI RUMAH SAKIT UMUM DAERAH TASIKMALAYA TAHUN 2011 DAN 2012 - Dian Budi Santoso; Angga Eko Pramono; Agasi Gilang Persada (Asosiasi Perguruan Tinggi Rekam Medis dan Informasi Kesehatan Indonesia- APTIRMIKI, 2014)
ABSTRACTHospitalization Unit is an important unit for hospital. One of the activities that must be performed by hospitalstatistics is to calculate the level of efficiency of a bed hospitalization unit, the parameters used are the BedOccupancy Rate (BOR), Average Length of Stay (AvLOS), Turn Over Interval (TOI), Bed Turn Over (BTO) andBarber Jonhson coordinate points in the third class care general of hospital Tasikmalaya in 2011 and 2012.The descriptive research uses secondary data with a retrospective approach, conducted on one variable thatis the use of a bed in the third class care of general hospital Tasikmalaya in 2011 and 2012.The sample is recapitulation of daily hospitalization census data in 2011 and 2012, which is based ontabulations. Collecting data using compurized calculation and presentation of Barber Johnson graphs. Resultsshowed that the BOR in 2011 was 114,31% and the increase accured in the 2012 as much as 121,01%, theAvLOS in 2011 was 4,46 and 4,41 days in 2012, the TOI was -0,37 days in 2011 and in 2012 was -0,48 days,while for values BTO in 2011 was 141,2 and in 2012 was 160,9. The conclusion is the use of a bed in a thirdclass care of general hospital Tasikmalaya in 2011 and 2012 is un-efficient.The key words: Efficient use of beds, BOR, AvLOS, TOI, BTO and Barber Johnson coordinate points